Rancangan Walker Menggunakan Pendekatan Ergonomi Partisipatori dan Matriks House of Quality sebagai Upaya Meningkatkan Kualitas Hidup Lansia - Beta Arya Ash Shidik; Yohandika Tri Apriliyanto; Aniya Maulani; Raiza Nur Inda Fiqri; Wirujiono; Dwi Dani Bayu Gusdana (UM Purwokerto Press, 2026)
Ensuring healthy lives and improving the well-being of people of all ages is one of the focuses of the Sustainable Development Goals (SDGs). The elderly population is aged 60 years and above and has higher functional mobility limitations because the elderly have difficulty walking and are more prone to falls. A Walking Frame (walker) is a walking aid for the elderly, which is proven to help the elderly improve body balance and reduce the risk of falling. However, it is known that walking aids (walkers) still have shortcomings when used outside the home, such as the walker not being equipped with a seat, the walker not being equipped with storage space, the walker being difficult to carry, and the walker being difficult to maneuver. Therefore, a redesign of walking aids is necessary to better meet the needs of older adults during outdoor activities. A participatory ergonomics approach and a House of Quality (HoQ) matrix were used in the design process for walking aids. The results of the study show that the elderly need walking aids that are easy to use, safe, multifunctional, portable, and durable. Specifications of the proposed walking aid: This walking aid has 4 wheels with a diameter of 20 cm; Dimensions of the walking aid (length 79.5 cm, width 48 cm, height 85 cm – 100 cm); The walking aid can be folded into a more practical shape; The walking aid is equipped with a seat, storage space, and a drinking bottle holder; The walking aid can be used as a walking aid with or without rear wheels. The statistical test results of the proposed walking aid are superior to those of the existing walking aids 1 and 2 in terms of ease of use, safety, multifunctionality, and durability. However, the portability aspects of the proposed walking aid and the existing walking aids 1 and 2 are at the same level.